2021
DOI: 10.1089/end.2020.1077
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Ureteral Access Sheath Use Within a Statewide Collaborative and Its Effect on Surgical and Clinical Outcomes

Abstract: Introduction: Ureteral access sheaths (UASs) are frequently used during ureteroscopy (URS), but their use is not without potential risk. We investigated patterns of UAS use and associated outcomes across practices in Michigan within a quality improvement collaborative. Methods: The Michigan Urological Surgery Improvement Collaborative (MUSIC) Reducing Operative Complications from Kidney Stones (ROCKS) initiative maintains a web-based, prospective clinical registry of patients undergoing URS for urinary stone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
0
19
0
2
Order By: Relevance
“…UASs were used in 1969 (37.7%) cases. After adjusting for clinical and surgical risk factors, UAS use decreased the odds of being stone free (OR = 0.75) [ 24 ]. Second, Kahraman et al evaluated factors affecting the success of RIRS in 46 children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…UASs were used in 1969 (37.7%) cases. After adjusting for clinical and surgical risk factors, UAS use decreased the odds of being stone free (OR = 0.75) [ 24 ]. Second, Kahraman et al evaluated factors affecting the success of RIRS in 46 children.…”
Section: Resultsmentioning
confidence: 99%
“…The Michigan Urological Surgery Improvement Collaborative (MUSIC) Reducing Operative Complications from Kidney Stones (ROCKS) initiative retrospectively investigated patterns of UAS use and associated outcomes across practices in 5316 ureteroscopy procedures. UASs were used in 1969 (37.7%) cases and were associated with increased odds of postoperative emergency department visits (OR = 1.50) and hospitalization (OR = 1.77) after adjusting for clinical and surgical risk factors [ 24 ]. Factors associated with post-ureteroscopy opioid prescriptions in 13,143 patients following RIRS included use of a UAS, besides year, younger age, male sex, higher BMI, absence of a pre-operative ureteral stent and stent placed during surgery [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, long-term follow-up data are lacking, and there remain concerns regarding trauma incurred to the urothelium with subsequent stricture formation and risk of early postoperative complications such as infection and pain. 51,52 In 2021, Meier et al 53 shared findings from a state-wide study, which included data from over 5000 URS procedures and revealed that UAS use significantly increased risk of hospital visit and did not increase likelihood of becoming stone free. Recent meta-analysis by Huang et al, 54 which included data from eight trials and over 3000 patients, concluded that use of UAS does not lead to any significant difference in SFR but was associated with higher complication rates.…”
Section: Ureteral Access Sheathsmentioning
confidence: 99%
“…Nevertheless, complications associated with RIRS cannot be underestimated – not only because of its continuously increasing use but also because of their potential severity ( 15 ). Ureteral access sheath (UAS) facilitates fragment basketing if the surgeon opts for stone fragmentation and provides a better irrigating flow – which is essential for better visualization and maintenance of pelvicalyceal temperature and low pressure and therefore might play an active role in the procedure success ( 16 18 ). However, Traxer et al reported on an overall incidence of UAS related ureteral lesions of 46.5%, of which 13.3% were classified as severe ( 19 ).…”
Section: Commentmentioning
confidence: 99%
“…Furthermore, a recent publication showed that UAS increased the odds of a post-operative emergency department visit and re-hospitalization, without better SFR ( 18 ). Unusual but dramatic complications related to the UAS have been described, such as the entrapment of a flexible ureteroscope (fURS) inside the sheath due to a breakage of the outer surface of the scope caused by excessive manipulation ( 20 ).…”
Section: Commentmentioning
confidence: 99%